Effects of asymmetric loading on lateral spinal curvature in young adults with scoliosis: A preliminary study - Li, Simon SW; Chow, Daniel HK (Prosthetics and orthotics international, 2018)
Background: Usual guidelines recommend symmetric load carriage over asymmetric load carriage. Whether this recommendation is valid for subjects with asymmetric body alignment, such as those with scoliosis, remains unclear. Scoliosis is both a subject-dependent and time-variant condition. Interventions are generally employed to prevent the abnormal spinal curvature from progressing. Objectives: To investigate the effects of an asymmetric load carriage on lateral spinal deformity in participant with scoliosis. Study design: Repeated measure and single-case experimental designs Methods: Photogrammetry was employed to measure the scoliotic curvature changes in thoracic and lumbar regions without a load (0%) and with a single-strap cross-chest bag loaded at 2.5%, 5%, 7.5%, 10% and 12.5% of body weight. Statistical tests and programming models were adopted to determine the loading conditions (placement and weight of the bag) with optimal and minimal corrections of the affected and unaffected scoliotic spinal regions, respectively. Results: Significant short-term postural correction of scoliosis was achieved through applying an asymmetric load on the ipsilateral shoulder relative to the apex location of the major scoliotic curve. Conclusion: A subject-specific optimal loading configuration was determined using a programming model. The results suggest that the application of a properly controlled asymmetric load carriage might be possible for reducing scoliotic spinal curvature. Further study of the long-term effects of subject-specific optimal asymmetric load carriage on scoliotic spinal curvatures is warranted. Clinical relevance Short-term reduction of scoliotic spinal curvatures under asymmetric load carriage was demonstrated. Thoracic curvatures could be reduced when asymmetric loading was applied on the ipsilateral shoulder relative to the scoliotic apex. Multiobjective programming was applied to determine the optimal weight of asymmetric load for participant with scoliosis.